2013
DOI: 10.5120/12131-8527
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Software Development Security Engineering using Dynamic System Method (DSDM)

Abstract: Agile methodology such as Scrum, Extreme Programming (XP), Feature Driven Development (FDD) and the Dynamic System Development Method (DSDM) have gained enough recognition as efficient development process by delivering software fast even under the time constrains. However, like other agile methods DSDM has been criticized because of unavailability of security element in its four phases. In order to have a deeper look into the matter and discover more about the reality, we conducted a literature review. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…[8] Design implementation is complex and it has also produced the security vulnerabilities within the system. [13] Interaction with consumers and changing decision has caused the delay schedule in project. [20] Software design and the documents have influenced the requirements change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Design implementation is complex and it has also produced the security vulnerabilities within the system. [13] Interaction with consumers and changing decision has caused the delay schedule in project. [20] Software design and the documents have influenced the requirements change.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the source code is one of the difficult tasks in the agile software development and it is also responsible for the normal execution of the functionality. Simplifying the design or code is critical process and it has the negative impact on the performance of an organization [13]. If the implementation of design is highly complex, the security vulnerabilities will exist within the system increases.…”
Section: Types Of Design and Code Changesmentioning
confidence: 99%
“…They had concluded that the existing extreme programming practices are not adequate in term of security, hence new XP practices based upon security require to be proposed. Sani [9] conducted a literature survey on DSDM in term of security incorporated in it. From literature they had spotted that currently DSDM lack behind in providing support for secure development of software's.…”
Section: Related Workmentioning
confidence: 99%
“…From above literature, it is extracted that the majority of studies focus on a particular agile practice such as XP, DSDM, FDD in their reviews [1,10,9,11]. And their focus is to identify that how much work is regarding security integration in agile or in particular agile practices and secondly scope of some studies [12,13] are limited to fewer number of research papers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation